Announcing the New: The Presence of the Soviet Dream in Chile (1927-1943) - Loyola-Tapia, M (STATE ACAD UNIV HUMANITIES, 2018)
Using printed sources and official archives, this article explores the Association of Friends of the USSR, an entity of communist affiliation that acted in Chile during the first part of the 20th century. Bearing in mind that the Russian Revolution of October 1917 and the deployment of the Soviet Union were fundamental milestones in the constitution of the identity and image of Chilean communist militancy, we propose an approach to the facts and actions that materialized this internalization and, on the way, how the construction of the Soviet became present in the politics of the country in that period.